2020
DOI: 10.1002/cmdc.202000018
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin‐Rasagiline Hybrids as Potent and Selective hMAO‐B Inhibitors, Antioxidants, and Neuroprotective Agents

Abstract: The frequency, complexity and morbidity of neurodegenerative diseases make them a great challenge for nowadays medicine. Most of the treatments currently used for Parkinson's disease – the second most prevalent – are only symptomatic. Therefore, it is urgent to develop drugs that are able to act simultaneously on different targets, being able to stop neuronal death and promote the recovery of neuronal populations already affected. In this work, we studied the activity of a series of hybrid molecules, which com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Some 3‐amidocoumarins already reported by the group were described as reversible h MAO‐B inhibitors [23] . Recently, a coumarin derivative bearing a pent‐2‐yn‐1‐amine group at position 7, the same position under study in this project, was reported as a partially reversible MAO‐B inhibitor [26] …”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Some 3‐amidocoumarins already reported by the group were described as reversible h MAO‐B inhibitors [23] . Recently, a coumarin derivative bearing a pent‐2‐yn‐1‐amine group at position 7, the same position under study in this project, was reported as a partially reversible MAO‐B inhibitor [26] …”
Section: Resultsmentioning
confidence: 80%
“…Their multitarget profile, especially regarding neurodegenerative disease, has already been described by several groups working in the field [12–15] . For more than ten years, our research group has been reporting differently substituted coumarins as monoamine oxidase (MAO), [16–20] acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) inhibitors, as well as neuroprotective agents (Figure 1A–D) [21–26] . Furthermore, 7‐substituted coumarins have been raised as potent multitarget molecules [27–31] .…”
Section: Introductionmentioning
confidence: 85%
“…The propargyl group is an alkylamine which is a bioactive moiety present in irreversible MAO‐B inhibitors rasagiline and selegiline. An effort was made by (Matos et al., 2020) to join the propargyl group of rasagiline with the coumarin nucleus (Figure 16). Compounds with the propargyl group being substituted at position 3 of coumarin ( 35a ) and position 7 ( 35b and 35c ) were found to be selective MAO‐B inhibitors.…”
Section: Coumarin With Fda‐approved Drugsmentioning
confidence: 99%
“…Some of these compounds display potent antioxidant activity and, therefore, could protect cells from neurodegeneration [ 10 ]. In the last few years, our group has described different series of 3-substituted coumarins displaying these properties [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…4.2.13. Synthesis of 6,7-Dihydroxy-3-(7-(2 ,4 ,5 -trihydroxyphenyl)-3,5-dioxohepta-1,6dien-1-yl)coumarin(16)…”
mentioning
confidence: 99%